ELECTROMECHANICAL SYNERGY: ADVANCED MODELING OF COUPLED ELECTRICAL–MECHANICAL ENERGY SYSTEMS - Rusman Rusman; Ava Lee; Sarah Williams (Yayasan Adra Karima Hubbi, 2026)
Electromechanical energy systems increasingly underpin modern transportation, industrial automation, and renewable power technologies, yet their behavior is often modeled through simplified decoupled approaches that overlook dynamic interaction between electrical and mechanical domains. This study aims to develop and evaluate an advanced modeling framework that explicitly represents electromechanical synergy as a bidirectional and nonlinear energy exchange process. The research employs a quantitative, model-driven methodology integrating electromagnetic equations, mechanical dynamics, and coupling coefficients within a unified simulation environment. Representative electromechanical systems are analyzed under steady-state and transient operating conditions to assess model accuracy and system behavior. The results demonstrate that coupled modeling significantly improves predictive accuracy for torque response, angular velocity, vibration behavior, and system stability compared to conventional decoupled models. The findings also reveal that coupling effects intensify during transient excitation and load variation, confirming the central role of interaction dynamics in system performance. The study concludes that electromechanical systems should be treated as integrated energy structures rather than isolated subsystems. Advanced coupled modeling provides a robust analytical foundation for design optimization, control development, and reliability assessment in complex energy systems. These contributions support future interdisciplinary research and facilitate practical implementation across emerging electromechanical applications worldwide in diverse industrial academic settings.